Muqarnas. - Aga Khan Program for Islamic Architecture (New Haven Yale University Press, 1983)
Annual
"An annual on Islamic art and architecture."
Sponsored by: the Aga Khan Program for Islamic Architecture at Harvard University and the Massachusetts Institute of Technology.
Keywords: Art, Islamic -- Periodicals; Architecture, Islamic -- Periodicals